Quinic Acid‐Conjugated Nanoparticles Enhance Drug Delivery to Solid Tumors via Interactions with Endothelial Selectins. Issue 50 (9th November 2018) - Xu, Jun; Lee, Steve Seung‐Young; Seo, Howon; Pang, Liang; Jun, Yearin; Zhang, Ruo‐Yu; Zhang, Zhong‐Yin; Kim, Pilhan; Lee, Wooin; Kron, Stephen J.; Yeo, Yoon
Abstract: Current nanoparticle (NP) drug carriers mostly depend on the enhanced permeability and retention (EPR) effect for selective drug delivery to solid tumors. However, in the absence of a persistent EPR effect, the peritumoral endothelium can function as an access barrier to tumors and negatively affect the effectiveness of NPs. In recognition of the peritumoral endothelium as a potential barrier in drug delivery to tumors, poly(lactic‐co‐glycolic acid) (PLGA) NPs are modified with a quinic acid (QA) derivative, synthetic mimic of selectin ligands. QA‐decorated NPs (QA‐NP) interact with human umbilical vein endothelial cells expressing E‐/P‐selectins and induce transient increase in endothelial permeability to translocate across the layer. QA‐NP reach selectin‐upregulated tumors, achieving greater tumor accumulation and paclitaxel (PTX) delivery than polyethylene glycol‐decorated NPs (PEG‐NP). PTX‐loaded QA‐NP show greater anticancer efficacy than Taxol or PTX‐loaded PEG‐NP at the equivalent PTX dose in different animal models and dosing regimens. Repeated dosing of PTX‐loaded QA‐NP for two weeks results in complete tumor remission in 40–60% of MDA‐MB‐231 tumor‐bearing mice, while those receiving control treatments succumb to death. QA‐NP can exploit the interaction with selectin‐expressing peritumoral endothelium and deliver anticancer drugs to tumors to a greater extent than the level currently possible with the EPR effect. Abstract : To overcome the endothelial barrier when accessing tumors, polymeric nanoparticles (NPs) are modified with a quinic acid (QA) derivative, synthetic mimic of selectin ligands, via polydopamine. The QA‐decorated NPs interact with selectin‐overexpressing endothelial cells and induce a transient increase in endothelial permeability to translocate across the endothelial layer. The QA‐NPs reach selectin‐upregulated tumors, achieving greater tumor accumulation and paclitaxel delivery than polyethylene glycol‐decorated NPs.